2014
DOI: 10.1097/inf.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Genetic Variants in Toll-like Receptor 2 Subfamily With Allergy and Asthma After Hospitalization for Bronchiolitis in Infancy

Abstract: In this study, we demonstrated that TLR1 rs5743618 was associated with asthma and atopic eczema during the first 6 years of life after early bronchiolitis. In addition, TLR6 rs5743810 was associated with present atopy at preschool age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 25 publications
5
39
1
Order By: Relevance
“…We have also shown previously that early- and late-onset asthma exhibit different clinical characteristics in our study21. Our findings were also consistent with several other studies that have also found some evidence of an association between TLR6 -rs5743810 T-allele and atopic asthma9, allergic rhinitis22 and allergic sensitisation23 in children.…”
Section: Discussionsupporting
confidence: 93%
“…We have also shown previously that early- and late-onset asthma exhibit different clinical characteristics in our study21. Our findings were also consistent with several other studies that have also found some evidence of an association between TLR6 -rs5743810 T-allele and atopic asthma9, allergic rhinitis22 and allergic sensitisation23 in children.…”
Section: Discussionsupporting
confidence: 93%
“…Review articles (n=28) were also excluded. Seventeen studies were excluded because they did not meet the inclusion criteria: eight did not report genotypic frequencies in cases and/or in controls24,25,38,43,44,45,46,47; two were cross-sectional studies48,49; four were family-based studies,50,51,52,53 and 3 were abstracts 54,55,56. Twenty case-control studies were eligible for meta-analysis,19,26,27,28,29,30,31,32,33,57,58,59,60,61,62,63,64,65,66,67 one study was in Portuguese,62 and another was in Chinese 64.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the association of polymorphisms with asthma varies depending on genetics, demographics, environmental factors, and study methodologies. Many association studies have reported that TLR polymorphisms predispose to asthma 26,47,49,52,56,59,61,68. However, some polymorphisms might not be associated with asthma susceptibility, but rather with asthma severity, such as TLR4 polymorphisms 48,51,58.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLRs 1, 2, 4, 5, 6, and 10 are located on the cell surface, whereas TLRs 3, 7, 8, and 9 are located inside the cells 9 , recognising microbial components after endocytosis. TLR1, TLR2, TLR6, and TLR10 comprise the TLR2 subfamily, and TLR1 , TLR2 , TLR6 , and TLR10 gene polymorphisms seem to play a role in susceptibility to asthma, atopic eczema, and allergic rhinitis 1012 . TLR3 recognises double-stranded viral ribonucleic acid (RNA), and, in mice, TLR3 activation by viruses combined with allergen inhalation resulted in allergic airway disease 13 .…”
Section: Introductionmentioning
confidence: 99%